The Child PTSD Symptom Scale among Yemeni School children: Factorial Validity - Ammar, Fawziah Kassim al-; Attal, Bothaina Ahemd; Ismail, Khamsiah (European Journal of Social Science Education and Research, 2024)
This study assessed factorial validity and reliability of an adapted Arabic version of the self-report of the Child CPSS Symptom Scale (CPSS-5-RS) based on the DSM-5. The sample included 902 displaced school boys (52%) and girls (48%) who had a mean age of 13.95 years (SD=2.3) in Sana’a city.  The participants had experienced internal conflict and airstrikes during a two-year period prior to the study (2015-2016). Principal Components Analysis, using Varimax rotation was conducted and yielded 19 items that loaded on three retained factors with an eigenvalue greater than one and explained 35.59% of the total of variance. Confirmatory Factor Analysis followed showing good fit indices (?2 (902) = 313.85, p?0.001, and CMINDF= 2 as desired with best-fit indices of TLI (.92), CFI (.94), IFI (.94) and RMSEA (.035).The internal consistency presents an acceptable reliability evidence that ranged from 0.73 for cognitive symptoms; 0.63 for emotional psychological symptoms, 0.60 for behavioral symptoms, and 0.78 for the total score. Further studies are needed to verify the findings in the different samples. Overall, the Arabic version of the CPSS is a sound, reliable and valid instrument that can be used by researchers and social workers to assess the symptoms of Posttraumatic disorders among the Yemeni children.
Keywords: trauma, PTSD symptoms, the CPSS scale, Yemeni schoolchildren, factorial validity